Can Big Data Analysis Make Cities Smarter? Emerging Issues and Stakeholder Implicationsin Smart Mobility - Gürsoy, Serkan; Yücelen, Murat (European Journal of Economics and Business Studies, 2017)
This study deals with the challenges and bottlenecks with respect to the concept of smart cities which has largelybeen constructed on knowledge utilization issues and challenges. Despite the abundant existent literature inthis field, the effective transformation of data into knowledge which can become a source of competitiveadvantage is still an ongoing debate, especially due to contemporary developments in big data analysismethods, approaches and strategies. As an emerging problem, the derivation of significant meaning from bigdata is among popular academic research fields, as well as being a crucial industrial and policy makingengagement regarding value creating mechanisms in smart cities. Therefore in this study, limitations andchallenges in translating big data into valuable knowledge in academia and industries are considered within theconcept of smart mobility. In an attempt to propose researchers, business firms and governmental entities acollaborative approach, a perception about emerging issues is presented for clarifying some future constructsintersecting in relevant research and applied fields.